IMPLEMENTASI METODE TSAQIFA DALAM PEMBELAJARAN MEMBACA AL-QUR'AN DI PESANTREN LANSIA NURUL IMAN - Maulana Prabo Daru; Joko Sarjono; S Sukari (Al'Ulum Jurnal Pendidikan Islam, 2021)
The purpose of this study was to determine the implementation of the "Tsaqifa Method". This study uses a qualitative descriptive data analysis method, with the research subject at the Nurul Iman Elderly Islamic Boarding School. In this study, data collection techniques through observation, interviews, and documentation. Meanwhile, data analysis uses data reduction, data presentation, and data verification. Based on the results of this study, it is explained that the implementation in learning to read the Qur'an with the book "Tsaqifa" does not have a special way or strategy in teaching it. It's just that in teaching this book an ustadz or teacher must master Arabic reading and recitation and extra patience, because in its implementation an ustadz or teacher must first explain one by one the hijaiyah letters. The inhibiting factors in the implementation of learning to read the Qur'an using the tsaqifa method book are: 1.) The process and memory of students are different. 2.) Inadequate facilities and infrastructure. 3.) Less active students. The efforts to overcome the difficulties of reading the Qur'an include: a.) Asatidz knows the nature and character of each student to make it easier to deliver in the learning process. b.) Asatidz must be more disciplined in the learning process. c.) Asatidz must often provide motivation and foster a sense of enthusiasm for the students.